Rice Husk Ash: Burning Procedures And Its Effect On Cementitious Properties Of Paste And Mortars - Jahaber, Mohamed Kassim (Universiti Teknologi Petronas, 2006)
Rice husk ash (RHA) is a waste material that needs costly disposal to avoid environmental pollution. Nevertheless RHA has basic oxide contents that have some cementitious properties. By and large through normal burning procedures, RHA contains about 80%-85% amorphous Si02, which is a vital cementitious element. The focus of this research is to establish a burning procedure to derive highly active amorphous silica from rice husk so that its pozzolanic reactivity can be enhanced. Numerous burning procedures have been employed for this purpose. Finally two methods of burning were established. Even though the temperatures of burning varied between the two procedures, both were based on the same principle of thermal combustion in three stages. In the first stage the burning temperature was capped at 280°C, which was less than the ignition temperature of rice husk in the presence of air. In the second stage, the temperature was maintained between 280°C and 520°C. The presence of air is essential to oxidize the residual carbon from the rice husk. In the third stage, the temperature was increased to 550°C but in the absence of air. The two procedures with burning duration of 184 minutes and 176 minutes yielded silica content of 93.1 % and 94.3% respectively. The XRD Test further confirmed that the silica was in amorphous form. The cement paste cubes containing RHA replacements of2.5%, 5%, 7.5%, 10%, 12.5%, 15%, 17.5% & 20% were tested and their compressive strengths were compared with control cement cubes. It was found that the percentages replacement of 5% and 7.5% of RHA with water/cement (w/c) of 0.28 and 0.32 respectively produced higher compressive strength compared with its control mix. The optimum w/c for cement paste cubes containing 2.5% RHA in order to get high strength was 0.25. For other replacement ratios of 5%, 7.5%, I 0%, 12.5%, 15%, 17.5% & 20% RHA, the corresponding w/c were 0.28, 0.32, 0.32, 0.35, 0.36, 0.37, and 0.39 respectively. Test on pozzolanic activity index of RHA was carried out and compared with RHAs that were obtained from other methods of burning. The pozzolanic activity index of this RHA was found to have higher value compared to RHA from ferrocementincinerator. The effect of RHA on porosity of cement cubes containing RHA was also investigated in this research and was found that RHA replacement with low w/c reduces porosity.